Dose-dependent effects of human umbilical cord-derived mesenchymal stem cell treatment in hyperoxia-induced lung injury of neonatal rats - Xiong, Jing; Ai, Qing; Bao, Lei; Gan, Yuanshan; Dai, Xiaoyu; Han, Mei; Shi, Yuan (Frontiers in Pediatrics, 2023)
Background Mesenchymal stem cells (MSCs) are multipotent stromal cells that have been reported to possess great potential for the treatment of bronchopulmonary dysplasia (BPD). Objective Our study aims to assess the effects of three different doses of intraperitoneal administration of human umbilical cord-derived MSCs (hUC-MSCs) on a hyperoxia-induced BPD model of newborn rat. Methods Neonatal Sprague Dawley (SD) rats were reared in either hyperoxia (75% O2) or room air (RA) from postnatal days (PN) 1-14. At PN5, hUC-MSCs (1 × 106, 5× 106,or 1× 107 cells per pup) were given intraperitoneally to newborn rats exposed to 75% O2 from birth; the controls received an equal volume of normal saline (NS). At PN14, the lung tissues, serum, and bronchoalveolar fluid (BALF) were collected for histologic examination, wet/dry (W/D) weight ratio analysis, engraftment, myeoloperoxidase (MPO) activity analysis, cytokine analysis, and western blot analysis of protein expression. Results Compared to rat pups reared in RA, rat pups reared in hyperoxia had a significant lower survival rate (53.3%) (P < 0.01). Hyperoxia-exposed rats exhibited pulmonary inflammation accompanied by alveolar-capillary leakage, neutrophile infiltration, augmented myeloperoxidase (MPO) activity, prominent alveolar simplification, and increased mean linear intercept (MLI), which was ameliorated by hUC-MSCs treatment. Increased oxidative stress and inflammatory cytokine production were also reduced. Importantly, the expression of Fas, an apoptosis-associated protein that was increasingly expressed in hyperoxia-exposed rats (P < 0.05), was downregulated after administration of hUC-MSCs (P < 0.05). Conclusions Our results suggest that intraperitoneal administration of high number hUC-MSCs (1 × 107 cells) may represent an effective modality for the treatment of hyperoxia-induced BPD in neonatal rats.